Reflective functioning and teacher burnout: the mediating role of self-efficacy. Issue 6 (2nd November 2021) - A. Dexter, Casey; Wall, Marnie
ABSTRACT: Teacher burnout is a mental state resulting from job strain that arises when teachers lack the adequate coping abilities to successfully handle the demands of the teaching profession. When compared to other professions, teachers exhibit high levels of exhaustion and cynicism, which are the core dimensions of burnout. Teacher self-efficacy is a well-established predictor of burnout, yet little research has investigated potential psychological predictors of self-efficacy. Reflective functioning is a psychological construct that reflects a cognitive ability to understand and analyze one's own and other peoples' behavior in the context of their mental states. The purpose of this study is to investigate the role that reflective functioning plays in predicting self-efficacy, and in turn, teacher burnout. Forty-six elementary school teachers in the United States participated in a cross-sectional, survey-based research study. Mediation analyses indicate an indirect effect between reflective functioning and teacher burnout, with teacher self-efficacy mediating this relationship. The findings from this study suggest teachers who are more reflective view themselves as more self-efficacious, which collectively prevents the gradual development of burnout. Future studies should further examine the relationships between these variables as it may have important implications for future teacher professional development initiatives.